FISHERY RESOURCES MANAGEMENT IN THE REPUBLIC OF INDONESIA’S FISHERY MANAGEMENT REGION 711 FOR THE SUSTAINABLE FISHERY RESOURCES CONTROL - Siregar, Nur Mar Atushsholihah; Swastanto, Yoedhi; Said, Budiman Djoko (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2019)
The Republic of Indonesia Fisheries Management Region is an area that intended for controlling the fisheries management activities. However, the potential value of fisheries in WPP-RI 711 has been decreasing starting from 2016 to 2017. The problems are about fisheries resource management activities in the region which are then linked to government policy control. This study seeks to determine the development of fisheries resource production in FMR-RI 711, the level of utilization based on management with the MSY and MEY models, and also control of sustainable fisheries policies. This study uses experimental quantitative methods with the Schaefer, Fox and Gordon models. Data obtained came from fisheries resource groups and data samples were taken from shrimp groups. The results of the analysis show that the average development of fisheries resource production in FMR-RI 711 has decreased even experienced overfishing in the commodity of Small Pelagic Fish and Crustaceans. The Schaefer model is considered the most appropriate because it has a determination coefficient value of 42.9% and has an optimum effort value of 179 trips/year, with the MSY value obtained at 3.8520 tons/year. The policy controls carried out so far are still very lacking and need to take firm action from the government in overcoming fisheries problems that are overfishing. Therefore, it can be concluded that fisheries management in FMR-RI 711 has not run optimally, then fisheries management should also be carried out by considering the economic aspects of fisheries, besides it also needs serious efforts on fisheries supervision and the development of a cost model to maintain resources from overfishing. Keywords: Fisheries management, Fisheries policy, FMR-RI 711